Using Global Englishes to Improve Listening Comprehension in Pre-intermediate English Learners (GIST – Education and Learning Research Journal, 2024)
This ​qualitative ​case study examined the impact of listening to Global Englishes on the development of listening comprehension in pre-intermediate English students at Universidad Nacional, ​     ​Costa Rica. Using questionnaires, focus groups, and ​observations​, the research explored students' perceptions of various English ​speakers from different nationalities ​and their overall experience with exposure to diverse global varieties. The findings indicated that students found ​     ​​English spoken by people from the ​​United​​​ ​States​, Mexico, and​     ​Venezuela easier to understand due to clarity and familiarity, while British, Australian, and Scottish​ variants ​presented the greatest challenges, particularly​ due to ​pronunciation. Students stated that the listening activities expanded their vocabulary and improved their comprehension skills by providing real-world exposure to English spoken in different regions. The results indicated the need for a shift in language teaching approaches in Costa Rica, emphasizing the inclusion of Global Englishes in curricula to better prepare students for international communication. Further research is recommended to investigate the long-term impact of this approach and its potential benefits in improving aural and oral skills.
Keywords: ​Listening comprehension; Global Englishes; lingua franca